Evaluating financial performance: ratio analysis and common-size financial statement analysis. A case of Composites Technologies Research Malaysia (CTRM) Aero Composites Sdn Bhd / Mohd Hashir Mohd Kamel - Mohd Kamel, Mohd Hashir (Faculty of Business and Management, 2009)
CTRM Aero Composites Sdn Bhd (CTRM AC) was incorporated on 16thAugust 1994. CTRM AC fully commenced its operations in 2000 under the name Aero-Composites Technologies Sdn Bhd. Its nature of business is to manufacture composites components for aero and no-aero structures. This project paper focus on the performance of company and the new or alternative financial evaluation methods for CTRM Aero Composites Sdn Bhd. Recently, Finance department of CTRM AC used Ratio Analysis as the main tools of evaluation. Data being collected by interview, journal and also experiment in order to test the new methods in company. Thus further studies being done to find the way of introducing the alternative methods of evaluation. There are two methods which have been used to evaluate financial performance of company such as Ratios Analysis and Common-Size Financial Statement Analysis. These two methods are used to compare financial statements of the same company over different periods. The result indicates that, the used of both methods contribute to the reasons and evidence that based on the trend of financial statement.